Genetic Code Expansion and Click-Chemistry Labeling to Visualize GABA-A Receptors by Super-Resolution Microscopy - Kuhlemann, Alexander; Beliu, Gerti; Janzen, Dieter; Petrini, Enrica Maria; Taban, Danush; Helmerich, Dominic A.; Doose, Sören; Bruno, Martina; Barberis, Andrea; Villmann, Carmen; Sauer, Markus; Werner, Christian (Frontiers in Synaptic Neuroscience, 2021)
Fluorescence labeling of difficult to access protein sites, e.g. in confined compartments, requires small fluorescent labels that can be covalently tethered at well-defined positions with high efficiency. Here, we report site-specific labeling of the extracellular domain of GABA-A receptor subunits by genetic code expansion (GCE) with unnatural amino acids (ncAA) combined with bioorthogonal click-chemistry labeling with tetrazine-dyes in HEK-293-T cells and primary cultured neurons. After optimization of GABA-A receptor expression and labeling efficiency, most effective variants were selected for super-resolution microscopy and functionality testing by whole-cell patch clamp. Our results show that GCE with ncAA and bioorthogonal click labeling with small tetrazine-dyes represents a versatile method for highly efficient site-specific fluorescence labeling of proteins in crowded environment, e.g. extracellular protein domains in confined compartments such as the synaptic cleft.